The Effect of Previous Irradiation for Patients With Prosthetic Breast Reconstruction: A Meta-Analysis. (23rd February 2021) - Hong, Wei-Jin; Zhang, Guo-Yi; Chen, Chun-Lin; Li, Fang-Wei; Wang, Hai-Bin
Abstract: Background: Results regarding immediate prosthetic breast reconstruction after postmastectomy radiation therapy (PMRT) have been inconsistent. Objectives: The authors aimed to assess the efficacy and safety of PMRT before immediate prosthetic breast reconstruction for patients with breast cancer. Methods: Electronic databases (PubMed, EmBase, and the Cochrane Library) were systematically searched to identify eligible studies from their inception until March 2020. The pooled odds ratio (OR) with 95% confidence intervals (CIs) was applied as an effect estimate and calculated using the random-effects model. Results: Nineteen studies including a total of 6757 patients were selected for final meta-analysis. The pooled OR showed that PMRT was associated with a higher incidence of reconstruction failure (OR = 2.57; 95% CI =1.55–4.26; P  < 0.001), capsular contracture (OR = 5.99; 95% CI = 3.12–11.47; P  < 0.001), and overall complications (OR = 2.52; 95% CI = 1.68–3.79; P  < 0.001). It was also associated with a lower incidence of patient satisfaction (OR = 0.29; 95% CI = 0.16–0.52; P  < 0.001) and good aesthetic results (OR = 0.25; 95% CI = 0.12–0.52; P  < 0.001) compared with those who did not undergo PMRT. These significant associations could be affected by study design, mean age, stage of immediate breast reconstruction, follow-up, and study quality. Conclusions: Although PMRT is the standard adjuvant therapy for mastectomy patients treated with immediate implant-based breast reconstruction, PMRT for patients undergoing immediate implant-based breast reconstruction has been associated with high risks of reconstruction failure, capsular contracture, and overall complications as well as low incidences of patient satisfaction and good aesthetic results. Level of Evidence: 4: